2017
DOI: 10.3390/su9050691
|View full text |Cite
|
Sign up to set email alerts
|

Energy Vulnerability Composite Index in Social Housing, from a Household Energy Poverty Perspective

Abstract: In Europe, the proportion of social housing is high, and such houses tend to be inhabited by below average-income households, which are particularly vulnerable to energy poverty. This article proposes a new methodological approach for defining an index for household energy vulnerability assessment. This method can be used to improve the management of social housing. After establishing a heuristic framework for household energy poverty-which stems from different causes such as income, the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…A firm's environmental goals of sustainability may concern energy consumption, water efficiency, toxic waste prevention, etc. In terms of sustainable renovation, many previous studies focus on the environmental aspects such as reducing energy use [4,16,17].…”
Section: Using the Tbl Model As An Evaluation Framework And Practicalmentioning
confidence: 99%
“…A firm's environmental goals of sustainability may concern energy consumption, water efficiency, toxic waste prevention, etc. In terms of sustainable renovation, many previous studies focus on the environmental aspects such as reducing energy use [4,16,17].…”
Section: Using the Tbl Model As An Evaluation Framework And Practicalmentioning
confidence: 99%
“…Energy efficiency Ratio of end-use energy to Bangladesh, China, Germany total energy [54,55] Energy gap (difference between Portugal, Global South, building's energy demand Attika(Greece), China, Germany and consumption) [45,47,55,59] Type of heating/cooling system [42,45,48,50,55,59] Greece, Global South, Attika(Greece), Spain, Zaragoza(Spain), China, Germany dwelling insulation against EU, Global South the cold/warm [27,41,59] Belgium…”
Section: Category Indicator Country/region Applied Tomentioning
confidence: 99%
“…Year of house construction Greece, Japan, Portugal, (housing's age) [42,[45][46][47][48]59] Global South, Attika(Greece), Zaragoza(Spain)…”
Section: Category Indicator Country/region Applied Tomentioning
confidence: 99%
“…Several researchers have recently applied housing indicators in order to achieve or enhance sustainability [16][17][18][19][20][21][22][23]; some of these investigations refer to social housing [17,18,21,22]. Among the indicators that were analyzed are those referring to household vulnerability; these studies found that social housing tends to be inhabited by people with below-average incomes [18,21] who are vulnerable to energy poverty. To solve this issue, Llera-Sastresa proposed a methodological approach based on indicators that improves energy management in social housing [21].…”
Section: Background and Research Objectivesmentioning
confidence: 99%